Ângelo de Sousa’s photographic and film collection: strategies for the preservation of colour slide-based artworks - Silva, Joana Santos Lima da (2019)
The Portuguese artist Ângelo de Sousa (1938-2011) produced noteworthy work in photography and experimental film. However, a lack of in-depth studies focusing on the use of these media by the artist is acknowledged. Thus, his work has been studied, particularly through unpublished documentation found in the artist’s house and in public archives, bringing new insights into his production. Despite the delay in the artistic context felt in Portugal in the post-modern period, Ângelo de Sousa produce photographic and film work perfectly in line with that of other international artists. The slide-based artwork Slides de Cavalete (1978-1979), constructed with the additive synthesis of colours, stands out as an example of the inventiveness achieved by the artist with these media. The production process behind Slides de Cavalete has been studied and reproduced, allowing for a thorough understanding of the work and contributing to the definition of its significance. The photographs and films have been gathered together in his house. Since typologies, quantities and condition of the materials were unknown, a survey was carried out to enhance knowledge of the collection and to define preservation priorities. Accordingly, 35 mm chromogenic reversal films (slides), used to produce almost all his photographic colour work, was highlighted as the set in highest risk due to colour change detected in one third of these materials. Thereby, slide-based artworks by Ângelo de Sousa were studied in further detail. The display options undertaken by the artist during his lifetime have been investigated, in order to guide the decision-making process regarding the exhibition and preservation of his slide-based artworks. Slides de Cavalete was selected as a case study, and the history of its exhibition was assessed by searching for documentation and interviewing people. Thus, it is understood that the work was first presented projected on a canvas over an easel, in 1979. Since the artist’s death, the work has been presented without this setup, and recently, as a digital projection. An exhibition was conducted at FCT NOVA, to test the variability of the work displayed with a digital and a slide projector. Based on a questionnaire, a clear preference for the slide projection was acknowledged. Thus, guidelines for the exhibition of Slides de Cavalete are defined, following its first presentation. Considering that chromogenic reversal films are highly susceptible to colour change and that there is still much to know about these materials, their molecular characterization and degradation has been studied. Different pathways to characterize chromogenic dyes are suggested based on chromatographic and spectroscopic techniques. Additionally, a methodology to accurately monitor colour change in these materials has been defined, based on samples artificially aged at different temperatures (50, 60, 70 and 80˚C) and relative humidity (40% and 60%). The samples were assessed using spectrophotometry with optical fibre probes in the ultraviolet-visible range. From the spectral data, intensity maximums, CIE L*a*b* coordinates and the total colour variation (ΔE*) have been determined. Optical microscopy and digitization have also proven useful for degradation assessment on these materials.